FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TINGKAT KELELAHAN PETUGAS PENANGANAN PRASARANA DAN SARANA UMUM (PPSU) DI WILAYAH KECAMATAN CILANDAK TAHUN 2022 - Putri Yasmin Rahmadiani, (2023)
Work fatigue is a health and safety problem that can be a risk factor for work accidents. Fatigue in officers can have an impact on decreasing work productivity and decreasing work concentration. This research was conducted to determine the factors associated with the level of fatigue of officers handling public infrastructure and facilities (PPSU) in the Cilandak District area. The study design used was cross-sectional. Data collection was carried out by filling out the Industrial Fatigue Research Committee (IFRC) questionnaire and measuring height, weight and pulse. The sampling technique was proportional stratified random sampling with 220 respondents. Statistical test using the Chi Square Test. Based on the results of the study, the frequency of work fatigue among PPSU officers was in the moderate category (83.6%). The results of the bivariate analysis showed that there was a relationship between the variables of nutritional status (p=0.002), workload (p=0.000) and work fatigue, while the variables were age (p=0.287), years of service (p=0.380), and ambient temperature (p= 0.056) has no relationship with work fatigue. It is hoped that PPSU officers will consume nutritious food to increase energy so they don't get weak at work and optimize rest time.